On fusion 2-categories - Décoppet, TD (2023)
The theory of fusion 1-categories has received much attention, and is therefore well established. Fusion 2-categories were recently introduced as a categorification of the notion of a fusion 1-category. The present thesis is devoted to the study of the general properties of fusion 2-categories.